Chronic cerebrospinal venous insufficiency is not associated with chronic venous disorders: A case–control study. (December 2015) - Leone, Maurizio A; Raymkulova, Olga; Lochner, Piergiorgio; Bolamperti, Laura; Rivadossi, Gianandrea; Stecco, Alessandro; Zaccala, Giuseppe; Maggio, Maurizio; Liboni, William; Guido, Marilena; Coppo, Lorenzo; Imperiale, Daniele
Objectives: To evaluate the relationship between chronic cerebrospinal venous insufficiency (CCSVI) and the presence of a Chronic Venous Disorder (CVD). Method: We included 55 subjects with CCSVI aged >18 years, and 186 controls without CCSVI. Each subject was evaluated with color Doppler sonography in accordance with Zamboni's five criteria, examined by two neurologists and interviewed with an ad-hoc designed form. The neurologists and the sonographers were mutually blinded. CVD were classified according to CEAP. Results: Mean age was 42 years (SD = 9) in cases and 43 years (10) in controls ( p  = ns). The odds ratios in subjects CCSVI were 0.6 (0.2–2.2) for CEAP 1, 0.9 (0.2–4.5) for CEAP 2, and 1.0 (0.6–1.9) for family history of varicose veins. The prevalence of CVD and, family history of varicose veins, was similar between cases and controls for each Zamboni criterion. Conclusions: We found no association of CCSVI with the presence of CVD or family history of varicose veins.